Intervention to Reduce Stress and Blood Pressure in Hypertension Patients - Gultom, Agustina Boru; Batubara, Arbani; Sihombing, Nurmala Hayati (Universitas Lambung Mangkurat, 2025)
Hypertension cases at the Mulyorejo Community Health Center, Deli Serdang Regency, continue to rise. The stress experienced by hypertensive patients with high blood pressure requires appropriate management. The community health center has implemented various health initiatives, but further efforts are needed. Therefore, efforts to reduce stress and blood pressure in hypertensive patients were crucial. This community service activity used a Participatory Action Research (PAR) approach to empower hypertensive patients through a progressive muscle relaxation intervention with classical music. Topics covered included understanding hypertension, stress, the relationship between stress and blood pressure, and the implementation of the progressive muscle relaxation intervention with classical music, packaged in a booklet. Before and after the intervention, community service personnel measured stress using the Subjective Units of Distress Scale (SUDS) and blood pressure using an Omron digital sphygmomanometer. The activity was conducted from June to July 2025. The target group was 40 adult hypertensive patients, divided into two groups of 20 participants each from Pujimulyo and Payageli Villages. Results: The Wilcoxon test showed a p-value of 0.0001 for stress and blood pressure, both systolic and diastolic. Participants responded positively to this intervention and will continue it at home. It can be concluded that progressive muscle relaxation intervention with classical music can significantly reduce stress and systolic and diastolic blood pressure in hypertensive patients. These findings indicate the need to integrate this intervention into routine programs at community health centers.